Avaliação do processo de fluoretação nos sistemas de abastecimento de água da região de Araçatuba, São Paulo - Daré, Flávio [UNESP]; Sobrinho, Milton Dall'Aglio [UNESP]; Libânio, Marcelo (FapUNIFESP (SciELO), 2009)
This paper focuses on the drinking-water fluoridation process in Araçatuba region water supply systems by means of 5.157 fluoride concentration data from 2001 to 2005. These data were studied based on the water source, the administration and the structure of the water supply system, according to the population of the county and the type of management. Almost half of samples did not comply the fluoridation standard and the higher compliance was verified in the water supply systems operated by Sabesp (69%), followed by the group of Large counties (52%), statistically similar to the Medium ones (51.4%), and better than the Small ones (28%). The systems with surface intakes showed statistically higher performance in the compliance to the standard (60%) compared to the ones that use groundwater (42.9%). In this last group, those that explore the Guarani aquifer were superior (52.3%) than the others (46.6%).
Evaluation of the fluoridation in the water supply systems of Araçatuba, São Paulo, Brazil
Keywords: Drinking-water quality; Drinking-water surveillance; Fluoridation; Optimum fluoride level